Low-melting-point glass composition, product and preparation method thereof
By developing low-melting point glass compositions containing alumina, silica and phosphorus pentoxide, the problems of the vulnerable properties of existing glass products in humid environments and the impact of high-temperature manufacturing on carbon are solved, and the preparation of wet-resistant glass products at lower temperatures and reducing carbon emissions are achieved.
Patent Information
- Application Number
- CN202411275318.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-09-09
- Filing Date
- 2024-09-12
- Publication Date
- 2025-03-14
AI Technical Summary
Existing glass products are prone to loss of their physical and chemical properties in humid environments, while the glass manufacturing process has a significant carbon contribution to atmospheric conditions and requires high temperature melting and molding.
A low melting point glass composition is developed in an amount ranging from about 1.5 mole% alumina to 5 mole%, 5 mole% silica to 45 mole% and phosphorus pentoxide is added to the glass composition using a phosphate compound to reduce the carbon footprint.
The preparation of glass products at significantly lower temperatures is achieved, reducing the carbon contribution of glass manufacturing to the environment, and maintaining the moisture resistance and chemical stability of glass.
Smart Images

Figure CN119612958A_ABST
Abstract
Description
CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to U.S. patent application No. 18 / 828,327 filed on September 9, 2024, which claims priority to U.S. provisional patent application No. 63 / 582,033 filed on September 12, 2023. Technical Field The present invention generally relates to novel low melting point glass compositions, glass articles containing the same, and methods for making the same. Background Art Millions of years ago, humans discovered the usefulness of naturally occurring glass. People learned how to make glass products more than 5,000 years ago. The modern usefulness of glass is very diverse and includes commercial and consumer uses. Glass is commonly used in commodity applications and technical applications related to the automotive industry, the electronics industry, spectroscopy, etc. Generally, glass products are also exposed to various chemical environments, and in order to ensure the long-term durability of the products, it is necessary to design glass compositions to withstand such environments. For example, glass products such as container glass, flat glass for windows, automobile windshields, laser matrix materials, fibers, tubing, etc. are used for commodity applications, such as bottles, vases, art and craft glass objects, etc., and are often subjected to environmental attacks of moisture and therefore can lose their initial properties. Therefore, it is necessary to be able to withstand exposure to moisture without losing its desired physical and chemical properties and products comprising the same. Furthermore, it is known that glass, through its manufacture, makes a significant carbon contribution to atmospheric conditions. The use of high heat forming processes of long duration results in this carbon contribution. Glass products typically require heat of about 1,450 degrees Celsius for the melting and forming processes. Therefore, there is a need for alternative glass compositions that can be used to produce glass products that can be formed at lower temperatures, thereby reducing the overall carbon contribution of glass manufacturing to the environment. The present disclosure at least in part satisfies these needs and other needs. Summary of the invention We are surprised to find that glass compositions can be prepared with significantly lower carbon footprints and at significantly lower temperatures. The molded glass can be used to form glass products (e.g., cans, bottles, glasses, drinkware, windows, etc.). In some embodiments, the glass composition may include about 1.5 mol% (mol%) aluminum oxide (Al2O3) to 5 mol% Al2O3 and 5 mol% silicon dioxide (SiO2) to 45 mol% SiO2. For example, the glass composition may include 1.5 mol% Al2O3 to 4 mol% Al2O3 or may include 2 mol% Al2O3 to 3.6 mol% Al2O3 or may include 2.8 mol% Al2O3 to 3.3 mol% Al2O3. In such exemplary embodiments, the silicon dioxide content may range from 5 mol% silicon dioxide (SiO2) to 15 mol% SiO2 (e.g., 5 mol% SiO2 to 10 mol% SiO2, 5 mol% SiO2 to 12 mol% SiO2, or 7 mol% SiO2 to 15 mol% SiO2, etc.). Embodiments of the glass composition may also include phosphorus pentoxide (P2O5). Phosphorus pentoxide may be added to the glass composition using a phosphate compound for forming a glass having the glass composition. For example, monosodium phosphate (also referred to as sodium hexametaphosphate), monopotassium phosphate, monocalcium phosphate, aluminum metaphosphate, dimagnesium phosphate, and / or other suitable sources of phosphorus pentoxide may be added to glass raw materials for forming glass, so that the glass has a glass composition having a desired content of P2O5 (e.g., a content of P2O5 within a preselected composition range of P2O5 or at a preselected P2O5 content). The use of these types of phosphate compounds may allow the formation of glass without the use of carbonate modifiers (e.g., CaCO3, Na2CO3, etc.), to help reduce the direct carbon footprint of the raw materials used to manufacture glass (having a preselected desired glass composition). In some embodiments, the glass composition may include less than 55 mol % P2O5 and greater than 35 mol % P2O5. For example, the glass composition may include a P2O5 content of 38 mol% P2O5 to 50 mol% P2O5 or a P2O5 content of 40 mol% P2O5 to 45 mol% P2O5. For example, some embodiments of the glass composition may include 5 mol% SiO2 to 10 mol% SiO2, 2.8 mol% Al2O3 to 3.3 mol% Al2O3, and 40 mol% P2O5 to 45 mol% P2O5. Other embodiments may utilize other combinations of the content ranges of SiO2, Al2O3, and P2O5 discussed herein (e.g., as discussed above or discussed below). Embodiments of the glass composition may also include other components. For example, embodiments of the glass composition may also include one or more modifiers. Examples of modifiers may include alkali metal modifiers, alkaline earth metal modifiers, and transition metal modifiers. For example, the modifier may include calcium oxide (CaO), magnesium oxide (MgO), zinc oxide (ZnO), sodium oxide (Na2O), iron oxide (Fe2O3), and / or potassium oxide (K2O). In some embodiments, the glass composition may include a total content of modifiers in the range of 40 mol% to 47 mol% (e.g., the total content of all such modifiers included in the glass composition may range from 40 mol% to 47 mol%). In other embodiments, the glass composition may include a total content of modifiers in the range of 30 mol% to 40 mol% or about 35 mol% (e.g., the total content of all such modifiers included in the glass composition may range from 30 mol% to 40 mol% or 33 mol% to 37 mol%, etc.). One or more modifiers may be included in the glass composition to help provide one or more properties to the glass composition that may help the glass be more efficiently used to make a particular type of article. For example, CaO and / or KO may be used as modifiers to help improve the durability of the glass having the glass composition. For example, a glass composition that may have a relatively low Al2O3 content may have a higher CaO content and / or a higher KO content. In some embodiments, the glass composition may have a CaO content of 22 mol% or greater (and not more than 47 mol% CaO). In some embodiments, K2O can be less than or equal to 10 mol% in the glass composition. Within such a range, the glass can be transparent (eg, avoiding opacity), and we have found that this type of composition range can help avoid phase separation. In some embodiments, Na2O may preferably not exceed 20 mol% of the glass composition. We have found that, in some cases, Na2O levels exceeding 20 mol% may cause the glass to be opaque and / or may degrade under ambient conditions. MgO, ZnO and / or CaO can be used in the glass composition to help provide a transparent and durable glass. For example, including CaO can help increase the Vickers hardness of a glass having the glass composition. We have found that glass compositions that do not contain divalents often result in the formation of opaque glass or glass that can degrade in air or ambient conditions, so many preferred embodiments can include one or more divalent modifiers. We have also found that modifiers with relatively high field strengths (e.g., Na2O, MgO, and ZnO) can help provide high crack resistance to glasses having the glass composition. Conversely, including CaO and / or K2O can reduce the crack resistance of the glass composition. For embodiments of glass compositions requiring high crack resistance, the glass composition can preferably have about 10 mol% CaO (e.g., 8 mol% CaO to 12 mol% CaO) and 15 mol% to 30 mol% ZnO and / or MgO (e.g., the content of ZnO and MgO can be 15 mol% to 30 mol%) in total. Modifiers may be selected to aid in coloration and other qualities. For example, in some embodiments, the alkali metal content of the glass composition may be no more than 14 mol% alkali metal to help avoid phase separation and avoid glass that may be blue (e.g., sky blue) or white in color. In some embodiments, having an alkali metal content of about 10 mol% may allow the glass to be compatible with various resistance melting techniques used to make glass. Examples of alkali metal modifiers include Na2O and K2O. Iron oxide (Fe2O3) can be used as a modifier in relatively small amounts to help improve durability and increase liquidus viscosity without adversely affecting the transparency of the formed glass or the processability of the glass. Some embodiments of the glass composition may include greater than 0 mol % Fe2O3 and less than 0.5 mol % Fe2O3. Including ZnO and MgO can have similar effects on the properties of glasses having the glass composition. Both modifiers can replace other modifiers (such as CaO) to help improve crack resistance and change durability. For example, in some embodiments, a higher MgO content can be present in the glass composition without ZnO. In other embodiments, a higher MgO content and a low ZnO content can be present in the glass composition. In yet other embodiments, a preselected MgO content and a relatively low ZnO content can be present. A higher alkali metal modifier content and a lower alkaline earth metal modifier content can result in a higher coefficient of thermal expansion for the glass compared to a glass having a lower alkali metal modifier content and a higher alkaline earth metal modifier content. The combination of modifiers for a particular application can be refined within the above content ranges to provide a desired glass composition for a glass article that can have a desired coefficient of thermal expansion for a particular application (e.g., for forming a particular type of article). In some embodiments, the glass composition including the modifier and P2O5 can be a glass composition having 9 mol% to 10 mol% SiO2 (e.g., 9.4-9.5 mol% SiO2), 40 mol% to 42 mol% P2O5 (e.g., 41.5-42 mol% P2O5), 2.8 mol% to 3.2 mol% Al2O3 (e.g., 2.85-3 mol% Al2O3), 24.5 mol% to 26 mol% CaO (e.g., 24.7- % PO, 2.89 mol % AlO, 24.90 mol % CaO, 2.83 mol % MgO, 8.52 mol % ZnO, 8.51 mol % NaO, and 1.13 mol % KO. As another example, an embodiment of the glass composition may include 9.46 mol % SiO, 41.76 mol % P2O5, 2.89 mol % Al2O3, 24.90 mol % CaO, 2.83 mol % MgO, 8.52 mol % ZnO, 8.51 mol % Na2O, and 1.13 mol % KO. As yet another example, a glass composition including a modifier and P2O5 can be a glass composition having 8 mol% to 11 mol% SiO2 (e.g., 9.4-9.5 mol% SiO2), 40 mol% to 42 mol% P2O5 (e.g., 41.5-42 mol% P2O5), 2.7 mol% to 3.4 mol% Al2O3 (e.g., 2.85-3 mol% Al2O3), 24 mol% to 26 mol% CaO (e.g., 24.7-25.3 mol% CaO), and 15 mol% to 30 mol% MgO. Some such embodiments can also include 8. mol% to 9 mol% Na2O (e.g., 8.4-8.6 mol% Na2O), and 1.0 to 1.5 mol% K2O (e.g., 1.08-1.2 mol% K2O). As yet another example, a glass composition including the modifier and P2O5 can be a glass composition having 8 mol% to 11 mol% SiO2 (e.g., 9.4-9.5 mol% SiO2), 40 mol% to 42 mol% P2O5 (e.g., 41.5-42 mol% P2O5), 2.7 mol% to 3.4 mol% Al2O3 (e.g., 2.85-3 mol% Al2O3), 15 mol% to 26 mol% CaO (e.g., 24.7-25.3 mol% CaO), 15 mol% to 30 mol% MgO, and no more than 5 mol% ZnO (e.g., 0-5 mol% ZnO, less than 3 mol% ZnO, and greater than 0 mol% ZnO, etc.). As yet another example, an embodiment of a glass composition including a modifier may have 9.46 mol% SiO2, 41.76 mol% P2O5, 3.2 mol% Al2O3, 24.90 mol% CaO, 2.83 mol% MgO, 8.52 mol% ZnO, 8.51 mol% Na2O, and 1.13 mol% K2O. As yet another example, an embodiment of a glass composition including a modifier may have 9.46 mol% SiO2, 41.76 mol% P2O5, 2.8-3.2 mol% Al2O3, 24.90 mol% CaO, 2.83 mol% MgO, 8.52 mol% ZnO, 8.51 mol% Na2O, and 1.13 mol% K2O. As yet another example, an embodiment of a glass composition including a modifier may have 9.46 mol% SiO2, 39.0 mol%-42.39 mol% P2O5, 2.09 mol%-3.0 mol% Al2O3, 25.28 mol% CaO, 9.71 mol% MgO, 1.18 mol% ZnO, 8.58 mol% Na2O, and 1.32 mol% K2O. As yet another example, an embodiment of a glass composition including a modifier may have 9.46 mol% SiO2, 41.76 mol% P2O5, 2.8 mol%-3.2 mol% Al2O3, 24.90 mol% CaO, 11.33 mol% MgO, 8.51 mol% Na2O, and 1.13 mol% K2O. As yet another example, an embodiment of a glass composition including a modifier may have 9-11 mol % SiO2, 39-43 mol % P2O5, 2.5 mol %-3.8 mol % Al2O3, 15-25 mol % CaO, 11-30 mol % MgO, 4-8 mol % Na2O, and 0.5-1.5 mol % K2O. In some embodiments, it is contemplated that higher amounts of Al2O3 may be desirable to promote desired melting conditions or desired mechanical properties (e.g., improved stability, etc.). In such embodiments, the glass composition may include, for example, 5-22 mol% Al2O3. For example, some embodiments of the glass composition may include about 25 mol% to about 55 mol% P2O5; about 5 mol% to about 45 mol% SiO2; about 5 mol% to about 22 mol% Al2O3; about 5 mol% to about 30 mol% ZnO; a total amount of greater than 0 to about 20 mol% Na2O, K2O, and / or lithium oxide (Li2O); about 2 mol% to about 8 mol% CaO and / or about 2 mol% to about 8 mol% MgO. Other embodiments may have other types of glass compositions. For example, a glass composition comprising: about 35 mol % to about 50 mol % (e.g., 35-50 mol %) of P2O5; about 5 mol % to about 15 mol % (e.g., 5-15 mol %) of SiO2; about 2 mol % to about 10 mol % (e.g., 2-10 mol %) of Al2O3; and a total amount of about 30 mol % to about 50 mol % (e.g., 30-50 mol %) of CaO, MgO, and ZnO may be provided for some embodiments. Still other embodiments of the glass composition can have about 25 mol % to about 55 mol % (e.g., 25-55 mol %) PO5; about 5 mol % to about 45 mol % (e.g., 5-45 mol %) SiO2; about 5 mol % to about 22 mol % (e.g., 5-22 mol %) Al2O3; about 5 mol % to about 30 mol % (e.g., 5-30 mol %) ZnO; a total amount of greater than 0 mol % to about 20 mol % (e.g., greater than 0 mol % to 20 mol %) Na2O, K2O, and / or Li2O; about 2 mol % to about 8 mol % (e.g., 2-8 mol %) CaO and / or about 2 mol % to about 8 mol % (e.g., 2-8 mol %) MgO. In yet other aspects, the glass compositions disclosed herein exhibit a melting point of less than about 1,400°C. Additionally, the glass compositions disclosed herein may include Fe2O3 in an amount up to about 10 mol%. Also disclosed herein is an article comprising a glass composition comprising from about 25 mol % to about 55 mol % PO; from about 5 mol % to about 45 mol % SiO; from about 5 mol % to about 22 mol % AlO; from about 5 mol % to about 30 mol % ZnO; a total amount of greater than 0 mol % to about 20 mol % NaO, KO, and / or LiO; from about 2 mol % to about 8 mol % CaO and / or from about 2 mol % to about 8 mol % MgO. In still further aspects, the articles disclosed herein may comprise tableware, cutlery, cookware, plate glass, windows, windshields, hollow vessels, jars, arts and crafts glass objects, laser-based materials, optical fibers, hollow fibers, tubing fibers, laboratory-usable containers, or any combination thereof. Also disclosed herein is a method comprising: a) providing: about 25 to about 55 mol % P2O5; about 5 to about 45 mol % SiO2; about 5 to about 22 mol % Al2O3; about 5 to about 30 mol % ZnO; a total amount of greater than 0 to about 20 mol % Na2O, K2O and / or Li2O; about 2 to about 8 mol % CaO and / or about 2 to about 8 mol % MgO; b) forming a homogeneous mixture; c) melting the mixture at a temperature of about 1,000°C to about 1,300°C; and cooling the composition to form any glass composition disclosed herein. Also disclosed herein are methods of forming articles comprising forming any of the above disclosed compositions. In still further aspects, the methods disclosed herein can exhibit at least about 25% reduction in CO2 emissions compared to a reference method of making a conventional soda-lime glass composition. In still further aspects, the glass composition is substantially free of alkali metal oxides. In still other aspects, the glass composition comprises up to a total of 10 mol% alkali metal oxides. In still further aspects, the glass compositions disclosed herein are substantially free of ZnO. In still further aspects, the glass composition exhibits a melting point less than about 1,300°C. Some embodiments may be formulated such that the formed glass is transparent. Other formed glasses may be colored via at least one colorant or additive. Also disclosed herein are articles comprising glass compositions that can provide compositions having any of the above-described glass compositions for articles. For example, the glass of the article can include about 35 mol% to about 50 mol% P2O5; about 5 mol% to about 15 mol% SiO2; about 5 mol% to about 10 mol% Al2O3; and a total of about 30 mol% to about 50 mol% CaO, MgO, and ZnO. As another example, the glass composition of the glass of the article can have 9 mol% to 10 mol% SiO2 (e.g., 9.4-9.5 mol% SiO2), 40 mol% to 42 mol% PO5 (e.g., 41.5-42 mol% PO5), 2.8 mol% to 3.2 mol% Al2O3 (e.g., 2.85-3 mol% Al2O3), 24.5 mol% to 26 mol% CaO (e.g., 24.7-25.3 mol% CaO), 2.7 mol% to 3.0 mol% MgO (e.g., 2.8-2.9 mol% MgO), 8.4 mol% to 8.7 mol% ZnO (e.g., 8.5-8.8 mol% ZnO), 8.2 mol% to 8.8 mol% Na2O (e.g., 8.4-8.6 mol% Na2O), and 1.0 mol% to 1.3 mol% KO (e.g., 1.08-1.2 mol% KO). In still further aspects, the articles disclosed herein may comprise tableware, cutlery, cookware, plate glass, windows, windshields, hollow vessels, jars, arts and crafts glass objects, laser-based materials, optical fibers, hollow fibers, tubing fibers, laboratory-usable containers, or any combination thereof. Also disclosed herein is a method comprising: a) providing raw materials for making glass to have one or more of the above-described glass compositions or other glass compositions disclosed herein, b) forming a homogeneous mixture; c) melting the mixture at a temperature of about 1,000° C. to about 1,300° C.; and cooling the composition to form any glass composition disclosed herein. Also disclosed herein are methods of forming articles comprising forming any of the above disclosed compositions. Some embodiments of the methods can be implemented to provide a reduction in CO2 emissions of about 15%-25% compared to a reference method of making a conventional soda-lime glass composition. In addition, the carbon footprint of the raw materials of glass that can be used to form the glass or glass article can be low. Additional aspects of the present disclosure will be explained in part in the following detailed description, drawings and claims, and in part will be derived from the detailed description or can be learned through practice of the invention. It is to be understood that the foregoing general description and the following detailed description are only exemplary and illustrative and are not limitations of the disclosed invention. BRIEF DESCRIPTION OF THE DRAWINGS Figure 1 (Also known as Figure 1 ) is a graph depicting an absorption spectrum of an exemplary glass composition according to an exemplary aspect. Figures 2A-2D (Also known as Figure 2A , Figure 2B , Figure 2C and Figure 2D ) is a graph showing relaxation behavior of an exemplary embodiment of a glass composition according to an exemplary embodiment. Figure 2A is a diagram illustrating the evaluation of the stretching parameter β (β), Figure 2B is a graph illustrating the evolution of viscosity, Figure 2C is a graph illustrating the evolution of the relaxation time, and Figure 2D is a diagram illustrating the simulated thermal history. Figure 3 and Figure 4 (Also known as Figure 3 and Figure 4 ) is a table illustrating exemplary embodiments of glass compositions. Figure 3 includes a table illustrating exemplary embodiments of glass compositions, and Figure 4 is a table illustrating exemplary embodiments of glass compositions. Figure 5 (Also known as Figure 5) is a graph illustrating the probability of crack initiation (PCI) as a function of load for a glass having a composition of an exemplary embodiment of a glass composition (which is identified as "Glass 1" in Table 2) and a conventional soda-lime glass. Figure 6 (Also known as Figure 6 ) is a series of photographs showing Figure 6 In the glasses having the composition of the exemplary embodiment of the glass composition identified as "Glass 1" in Table 2 in images (a), (b), and (c) and in Figure 6 Exemplary indentations made in conventional soda-lime glass in images (d), (e) and (f). Figure 6 The load applied to images (a) and (d) is 1 kgf. Figure 6 The load applied to images (b) and (e) is 0.5 kgf, and Figure 6 The load applied to images (c) and (f) is 0.1 kgf. Figure 7 (also referred to herein as Figure 7 ) is a graph showing how the coefficient of thermal expansion (CTE) of several exemplary embodiments of glass compositions varies with temperature compared to conventional soda-lime glass (SLS). DETAILED DESCRIPTION The present invention may be more readily understood by reference to the following detailed description, examples, drawings and claims and their preceding and following descriptions. However, before disclosing and describing the articles, systems and / or methods of the present invention, it is understood that unless otherwise stated, the present invention is not limited to the specific or exemplary aspects of the disclosed articles, systems and / or methods, as these may of course vary. It is also understood that the terminology used herein is for the purpose of describing particular aspects only and is not intended to be limiting. The following description of the present invention is provided as an enabling teaching of the present invention in its best, currently known aspects. For this reason, it will be recognized and appreciated by those skilled in the relevant art that many changes can be made to the various aspects of the present invention as described herein while still obtaining the beneficial results of the present invention. It will also be apparent that some desired benefits of the present invention can be obtained by selecting some features of the present invention without utilizing other features. Therefore, it will be recognized by those of ordinary skill in the relevant art that many modifications and adjustments to the present invention are possible, and may even be desirable and part of the present invention in some cases. Therefore, the following description is again provided as an illustration of the principles of the present invention rather than a limitation thereof. definition As used herein, the singular forms "a," "an," and "the" include plural referents unless the context clearly dictates otherwise. Thus, for example, reference to "an article" includes aspects having two or more such articles unless the context clearly dictates otherwise. It will be appreciated that for clarity, some features of the present disclosure described in the context of separate aspects may also be provided in combination in a single aspect. Conversely, for brevity, various features of the present disclosure described in the context of a single aspect may also be provided individually or in any suitable combination. As used herein, the terms "optional" or "optionally" mean that the subsequently described event or circumstance may or may not occur, and that the description includes instances where said event or circumstance occurs and instances where it does not. It is also understood that the terminology used herein is for the purpose of describing particular aspects only and is not intended to be limiting. As used in the specification and claims, the term "comprising" may include aspects of "consisting of" and "consisting essentially of". All technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs, unless otherwise defined. In this specification and the claims that follow, reference will be made to various terms defined herein. With respect to the terms "for example" and "such as" and their grammatical equivalents, unless expressly stated otherwise, they will be understood to be followed by the phrase "without limitation." Although the numerical ranges and parameters describing the wide range of the present disclosure are approximate values, the numerical values described in the specific embodiments are reported as accurately as possible. However, any numerical value inherently contains some errors, which are necessarily caused by the standard deviation found in their respective test measurement results. In addition, when describing the numerical range of the range of variation herein, it is contemplated that any combination of these values including the values listed can be used. In addition, the range can be expressed as from "about" a specific value and / or to "about" another specific value in this article. When such a range is represented, another aspect includes from a specific value and / or to another specific value. Similarly, when values are expressed as approximations by use of the antecedent "about," it will be understood that the particular value forms another aspect. It will be further understood that the endpoints of each range are significant both relative to the other endpoint and independently of the other endpoint. Unless otherwise indicated, the term "about" means within 5% (e.g., within 2% or 1%) of the particular value modified by the term "about." Throughout the disclosure, various aspects of the present invention can be presented in range form. It should be understood that the description of range form is only for convenience and brevity, and should not be interpreted as a hard limit to the scope of the invention. Therefore, the description of the range should be considered to specifically disclose all possible sub-ranges and single values within the range. For example, the description of a range (e.g., 1 to 6) should be considered to specifically disclose sub-ranges such as 1 to 3, 1 to 4, 1 to 5, 2 to 4, 2 to 6, 3 to 6, etc., and single values within the range, such as 1, 2, 2.7, 3, 4, 5, 5.3, 6 and any whole and partial increments therebetween. This has nothing to do with the width of the range. As used herein, the term "composition" is intended to include a product containing the specified ingredients in the specified amounts, as well as any product resulting directly or indirectly from the combination of the specified ingredients in the specified amounts. It is understood that the term "glass composition" as disclosed herein refers to a glass that is melted to form the defined composition prior to forming a specific glass article. It is further understood that a glass composition as used herein is distinct from batch ingredients that are introduced into the mixture prior to forming the glass. In some aspects, the batch ingredients used to form the composition may include elements that are substantially absent from the glass composition. Unless specifically stated to the contrary, the weight percent (wt%) of a component is based on the total weight of the formulation or composition in which the component is included. In aspects describing glass compositions, the concentrations of constituent components (e.g., SiO2, Al2O3, B2O3, CuO, NiO, etc.) are given as mole percent (mol%) on an oxide basis unless otherwise stated. As used herein, the term "substantially" means that the subsequently described event or circumstance completely occurs, or that the subsequently described event or circumstance usually, typically, or approximately occurs. Still further, the term "substantially" may refer in some aspects to at least about 80%, at least about 85%, at least about 90%, at least about 91%, at least about 92%, at least about 93%, at least about 94%, at least about 95%, at least about 96%, at least about 97%, at least about 98%, at least about 99%, or about 100% of a property, component, composition, or other condition used to characterize or otherwise quantify an amount. In other aspects, as used herein, the term "substantially free" when used in the context of a composition or component of a composition that is substantially absent is intended to mean that the component is not intentionally batched and added to the composition, but may be present as an impurity with other components added to the composition. In these aspects, the term "substantially free" is intended to mean trace amounts that may be present in a batched component, for example, it may be present in an amount less than about 1% by weight of the material, such as less than about 0.5% by weight, less than about 0.1% by weight, less than about 0.05% by weight, or less than about 0.01% by weight, based on the total weight of the composition. As used herein, the term "substantially" in, for example, the context of "substantially the same" or "substantially similar" refers to a method or system or component that is at least about 90%, at least about 91%, at least about 92%, at least about 93%, at least about 94%, at least about 95%, at least about 96%, at least about 97%, at least about 98%, at least about 99%, or about 100% similar to a method, system or component as compared thereto. It is also to be understood that the compositions disclosed herein are generally expressed as oxides, however, it is to be understood that specific elements may exist in an ionic state. As used herein, the term glass transition temperature or T g Used interchangeably and defined as the inflection point of the differential scanning calorimetry (DSC) curve during the second heating period, where cooling and heating of the sample is carried out at a rate of 10°C / min, and expressed as a plot of heat flow (in mW) versus temperature (in °C). As used herein, the term "melting point" refers to the temperature at which the batch material completely melts to obtain a homogeneous liquid. According to glass industry practice, the melting point occurs at a liquid viscosity of about 10-20 Pa·s. The term "crack resistance" may refer to the force required for a Vickers indentation to produce a 50% chance of a corner crack in the glass. Crack resistance may refer to resistance to crack initiation and may be distinguished from resistance to crack propagation, which is often referred to as toughness. Phase separation can refer to the process by which glass separates into two different liquids. Phase separation can cause the glass to become opaque. Devitrification can refer to the process by which a glass partially or completely crystallizes. For example, devitrification occurs when the glass is kept below the liquidus temperature for an extended period of time. Devitrification can be significant when crystals are present in the glass. The viscosity of the glass can be high enough below the liquidus temperature that the crystals do not have enough time to nucleate during the forming process to avoid devitrification. Field strength can refer to the ratio of an atom's charge to its size. High field strength materials can have high charge and small size. Although aspects of the present invention may be described and claimed in specific statutory categories, such as the system statutory category, this is merely for convenience, and one of ordinary skill in the art will understand that each aspect of the present invention may be described and claimed in any statutory category. Unless otherwise expressly stated, it is never intended that any method or aspect set forth herein be interpreted as requiring its steps to be performed in a particular order. Therefore, in the claims or specification, where a method claim is not specifically stated to limit the steps to a particular order, it is never intended to infer the existence of an order in any respect. This applies to any possible non-explicit basis for interpretation, including logical content regarding the arrangement of steps or operational flows, simple meaning derived from grammatical organization or punctuation, or the number or type of aspects described in the specification. The present invention may be understood more readily by reference to the following detailed description of its various aspects and embodiments included therein and by reference to the drawings and their previous and following descriptions. The present invention may be understood more readily by reference to the following detailed description of its various aspects and embodiments included therein and by reference to the drawings and their previous and following descriptions. Composition In some aspects described herein, the glass composition comprises: about 25 to about 55 mol % P2O5; about 5 to about 45 mol % SiO2; about 5 to about 22 mol % Al2O3; about 5 to about 30 mol % ZnO; a total amount of greater than 0 to about 20 mol % Na2O, K2O, and / or Li2O; about 2 to about 8 mol % CaO and / or about 2 to about 8 mol % MgO. In other aspects, the glass composition can also include about 25 mol% to about 55 mol% PO, including exemplary values of about 26 mol%, about 27 mol%, about 28 mol%, about 29 mol%, about 30 mol%, about 31 mol%, about 32 mol%, about 33 mol%, about 34 mol%, about 35 mol%, about 36 mol%, about 37 mol%, about 38 mol%, about 39 mol%, about 40 mol%, about 41 mol%, about 42 mol%, about 43 mol%, about 44 mol%, about 45 mol%, about 46 mol%, about 47 mol%, about 48 mol%, and about 49 mol%. In further aspects, the glass composition can include about 5 to about 45 mol% SiO2, including about 6 mol%, about 7 mol%, about 8 mol%, about 9 mol%, about 10 mol%, about 11 mol%, about 12 mol%, about 13 mol%, about 14 mol%, about 15 mol%, about 16 mol%, about 17 mol%, about 18 mol%, about 19 mol%, about 20 mol%, about 21 mol%, about 22 mol%, about 23 mol%, about 24 mol%, about 25 mol%, about 26 mol%, about 27 mol%, about 28 mol%, about 29 mol%, about 30 mol%, about 31 mol%, about 32 mol%, about 33 mol%, about 34 mol%, about 35 mol%, about 36 mol%, about 37 mol%, about 38 mol%, about 39 mol%, about 40 mol%, about 41 mol%, about 42 mol%, about 43 mol%, about 44 mol%, about 45 mol%, about 46 mol%, about 47 mol%, about 48 mol%, about 49 mol%, about 50 mol%, about 51 mol%, about 52 mol%, about 53 mol%, about 54 mol%, about 55 %, about 24 mol %, about 25 mol %, about 26 mol %, about 27 mol %, about 28 mol %, about 29 mol %, about 30 mol %, about 31 mol %, about 32 mol %, about 33 mol %, about 34 mol %, about 35 mol %, about 36 mol %, about 37 mol %, about 38 mol %, about 39 mol %, about 40 mol %, about 41 mol %, about 42 mol %, about 43 mol %, and about 44 mol % are exemplary values. In yet a further aspect, the glass composition can include about 5 to about 22 mol % Al2O3, including exemplary values of about 6 mol %, about 7 mol %, about 8 mol %, about 9 mol %, about 10 mol %, about 11 mol %, about 12 mol %, about 13 mol %, about 14 mol %, about 15 mol %, about 16 mol %, about 17 mol %, about 18 mol %, about 19 mol %, about 20 mol %, and about 21 mol %. In still further aspects, the glass composition can include about 5 to about 30 mol% ZnO, including exemplary values of about 6 mol%, about 7 mol%, about 8 mol%, about 9 mol%, about 10 mol%, about 11 mol%, about 12 mol%, about 13 mol%, about 14 mol%, about 15 mol%, about 16 mol%, about 17 mol%, about 18 mol%, about 19 mol%, about 20 mol%, about 21 mol%, about 22 mol%, about 23 mol%, about 24 mol%, about 25 mol%, about 26 mol%, about 27 mol%, about 28 mol%, and about 29 mol%. Also disclosed herein are aspects wherein the glass composition comprises a total amount of Na2O, KO, and / or Li2O greater than 0 to about 20 mol%, including exemplary values of about 0.01 mol%, about 0.05 mol%, about 1 mol%, about 2 mol%, about 3 mol%, about 4 mol%, about 5 mol%, about 6 mol%, about 7 mol%, about 8 mol%, about 9 mol%, about 10 mol%, about 11 mol%, about 12 mol%, about 13 mol%, about 14 mol%, about 15 mol%, 16 mol%, about 17 mol%, about 18 mol%, and about 19 mol%. It should be understood that in some aspects, the glass composition may comprise only Na2O in any of the above amounts. In still further aspects, the glass composition may comprise only Li2O in any of the above amounts. In still further aspects, the glass composition may comprise only KO in any of the above amounts. In a further aspect, the glass composition may include Na2O and Li2O such that the total amount of Na2O and Li2O falls within the range disclosed above. In a further aspect, the glass composition may include Na2O and KO such that the total amount of Na2O and KO falls within the range disclosed above. In a further aspect, the glass composition may include KO and Li2O such that the total amount of KO and Li2O falls within the range disclosed above. In a further aspect, the glass composition may include Na2O, KO, and Li2O such that the total amount of Na2O, KO, and Li2O falls within the range disclosed above. In yet other aspects, glass compositions are also disclosed wherein CaO is present in an amount from about 2 mol % to about 8 mol %, including exemplary values of about 3 mol %, about 4 mol %, about 5 mol %, about 6 mol %, and about 7 mol %. In yet other aspects, the glass compositions disclosed herein can further include about 2 mol % to about 8 mol % MgO, including exemplary values of about 3 mol %, about 4 mol %, about 5 mol %, about 6 mol %, and about 7 mol %. It should be understood that in some aspects, the glass composition can include both CaO and MgO. While in other aspects, the glass composition can include CaO or MgO in any of the amounts described above. In a further aspect, the glass compositions disclosed herein are comparable in their characteristics and properties to conventional soda-lime-silicate glasses while exhibiting superior melting properties. It will be appreciated that the composition of conventional soda-lime-silicate glasses is known. Typically, with some minor deviations, soda-lime-silicate glasses comprise about 70-75 wt % SiO2, about 12-17 wt % Na2O, about 7-12 wt % CaO, greater than 0 to about 2.5 wt % Al2O3, greater than 0 to about 1.0 wt % K2O, greater than 0 to about 5 wt % MgO, greater than 0 to about 0.15 wt % Fe2O3, 0 to about 0.5 wt % TiO2, and in some cases 0 to about 0.5 wt % SO3. Soda-lime-silicate glass is known to have a melting point in the range of about 1400 to about 1450° C. In certain aspects, the glass compositions disclosed herein exhibit a melting point that is at least about 50° C., at least about 100° C., at least about 150° C., at least about 200° C., at least about 250° C., or at least about 300° C. lower than the melting point of conventional soda-lime-silicate glass compositions. In further aspects, the glass compositions disclosed herein exhibit a melting point that is less than about 1,400° C., less than about 1,350° C., less than about 1,300° C., less than about 1,250° C., less than about 1,200° C., less than about 1,150° C., or less than about 1,000° C. Without wishing to be bound by any theory, it is observed that glass compositions having phosphates in the disclosed range allow the disclosed low melting points to be achieved while maintaining sufficient chemical durability. In a further aspect, it is also observed that the disclosed range of silicates allows sufficient chemical durability without the need for high melting temperatures. It should be understood that sufficient chemical durability may be determined by the specific application. It should also be understood that the actual durability may depend on the exact glass composition and the specific conditions to which it is exposed. For example, but not limited to, the conditions may include the type of solvent in which the glass is present, the pH of the solvent, the presence of corrosive elements, temperature, etc. The durability may be adjusted according to the specific application. For example, a glass composition used to make an art product will have a different sufficient chemical durability than a product used as tableware or cookware or laboratory ware. In a further aspect, it was found that the amount of aluminum oxide disclosed was sufficient to maintain melting conditions and sufficient chemical durability. The aluminum oxide present in the disclosed range may also impart additional mechanical stability to the glass. In a further aspect, it has been discovered that the disclosed amounts of ZnO can also help improve the mechanical properties of the glass composition without imparting substantial color to the glass. In further aspects, and again without wishing to be bound by any theory, it is hypothesized that including alkali and alkaline earth metals in the disclosed amounts can aid in charge balance of the aluminum oxide tetrahedrons and further reduce the melting temperature of the disclosed glass compositions. In other aspects, the glass compositions disclosed herein may further include iron oxides. In certain aspects, the glass compositions may include up to about 10 mol% Fe2O3, including exemplary amounts of about 0.01 mol%, about 0.05 mol%, about 0.1 mol%, about 0.5 mol%, about 1 mol%, about 1.5 mol%, about 2 mol%, about 2.5 mol%, about 3 mol%, about 3.5 mol%, about 4 mol%, about 4.5 mol%, about 5 mol%, about 5.5 mol%, about 6 mol%, about 6.5 mol%, about 7 mol%, about 7.5 mol%, about 8 mol%, about 8.5 mol%, about 9 mol%, and about 9.5 mol%. In certain aspects, when Fe2O3 can be present in an amount up to about 0.5 mol%, exemplary amounts include about 0.01 mol%, about 0.02 mol%, about 0.03 mol%, about 0.04 mol%, about 0.05 mol%, about 0.06 mol%, about 0.07 mol%, about 0.08 mol%, about 0.09 mol%, about 0.1 mol%, about 0.15 mol%, about 0.2 mol%, about 0.25 mol%, about 0.3 mol%, about 0.35 mol%, about 0.4 mol%, and about 0.45 mol%. In these exemplary and non-limiting aspects, the glass composition can be substantially free of color. In other aspects, spectroscopic methods can be used to determine the specific color of the glass composition. In some exemplary and non-limiting aspects, when the glass composition is substantially colorless, the composition exhibits a wavelength of less than or equal to about 0.49 cm in the visible light range of about 400 to about 800 nm, including wavelengths of about 450 nm, about 500 nm, about 550 nm, about 600 nm, about 650 nm, about 700 nm, and about 750 nm. -1 The average absorption coefficient, including less than or equal to about 0.45 cm -1 , less than or equal to about 0.4cm -1 , less than or equal to about 0.35cm -1 , less than or equal to about 0.3cm -1 , less than or equal to about 0.25cm -1 and less than or equal to about 0.2 cm -1 Example values of . In yet other aspects, when the glass composition is substantially colorless, such composition exhibits a percent transmittance greater than about 80%, greater than about 85%, greater than about 90%, greater than about 95%, or even greater than about 99% over a wavelength range of about 400 nm to about 800 nm, including about 450 nm, about 500 nm, about 550 nm, about 600 nm, about 650 nm, about 700 nm, and about 750 nm. In other aspects, when Fe2O3 is present in an amount from about 0.5 to about 5 mol%, including exemplary amounts of about 0.6 mol%, about 0.8 mol%, about 0.9 mol%, about 1 mol%, about 1.5 mol%, about 2 mol%, about 2.5 mol%, about 3 mol%, about 3.5 mol%, about 4 mol%, and about 4.5 mol%, the composition can be translucent gray. In a further aspect, the composition may also include iron oxides of other valences, such as FeO or a combination of Fe2O3 and FeO. +2 and Fe +3 In some aspects where both are present, a specific ratio may be determined based on the desired color. In other aspects, the ratio may also be affected by the potential presence of other ions, such as but not limited to alkali metal ions or other intermediates. In other aspects, the composition may further include multivalent Mn, Cr, and / or Ni to achieve a desired color of the glass. It is understood that iron oxides are typically present in the batch product used to form the glass compositions disclosed herein. Without wishing to be bound by any theory, it has been found that while the presence of up to 0.5 mol% of iron oxides in conventional soda-lime-silicate glass results in a greenish coloration at the edges, the disclosed glass compositions are substantially colorless or exhibit a grayish coloration at the edges. In a further aspect, when the amount of ionic oxide is above about 0.5 mol%, the glass composition exhibits a translucent gray color. In a still further aspect, when the glass composition includes up to about 10 mol% of iron oxide, such composition turns black. For example, a black composition can be defined by color coordinates of L* from 20.0 to 40.0, a* from -1.0 to 1.0, b* from -5.0 to 2.0, etc. In further aspects, the glass compositions disclosed herein can include additional transition metals in various concentrations. In certain aspects, the additional transition metals can be present as salts or oxides. In some aspects, the composition can also include one or more transition metal oxides comprising oxides of copper, nickel, cobalt, chromium, silver, tin, or any combination thereof. It should be understood that such transition metals can be present in the composition at any known valence. In certain aspects, the one or more transition metal oxides are present in an amount up to about 2 mol%, including about 0.01 mol%, about 0.05 mol%, about 0.1 mol%, about 0.15 mol%, about 0.2 mol%, about 0.25 mol%, about 0.3 mol%, about 0.35 mol%, about 0.4 mol%, about 0.45 mol%, about 0.5 mol%, about 0.55 mol%, about 0.6 mol%, about 0.65 mol%, about 0.7 mol%, about 0.75 mol%, about 0.8 mol%, about 0.85 mol%, about 0.9 mol%, about 10 mol%, about 11 mol%, about 12 mol%, about 13 mol%, about 14 mol%, about 15 mol%, about 16 mol%, about 17 mol%, about 18 mol%, about 19 mol%, about 20 mol%, about 21 mol%, about 23 mol%, about 24 %, about 1.9 mol %, about 2.1 mol %, about 2.2 mol %, about 2.4 mol %, about 2.5 mol %, about 2.6 mol %, about 2.7 mol %, about 2.8 mol %, about 2.9 mol %, about 3.1 mol %, about 3.2 mol %, about 3.3 mol %, about 3.4 mol %, about 3.5 mol %, about 3.6 mol %, about 3.7 mol %, about 3.8 mol %, about 3.9 mol %, and about 3.95 mol % are exemplary values. In a further aspect, the glass composition can achieve a desired specific color when one or more transition metal ions are present. In other aspects, the glass compositions described herein can be translucent. In yet other aspects, within a wavelength range of about 400 nm to about 800 nm, including wavelengths of about 450 nm, about 500 nm, about 550 nm, about 600 nm, about 650 nm, about 700 nm, and about 750 nm, such exemplary and non-limiting glass compositions can exhibit a percent transmittance of less than about 85%, less than about 80%, less than about 75%, less than about 70%, less than about 65%, less than about 60%, less than about 55%, or less than about 50%. In other aspects, when copper, silver, gold and / or tin and / or their alloys are present in the composition, these metals can be reduced to allow nanoparticles to be generated in the formed glass. It should be understood that in some aspects, tin can be used as a buffer to maintain the redox state of copper, silver, gold and their alloys. In such exemplary aspects, the glass composition can include a plurality of nanoparticles. Without wishing to be bound by any theory, it is believed that in such exemplary and non-limiting aspects, the plurality of nanoparticles disclosed herein can provide coloring to the glass through the effect of surface plasmon resonance. In other aspects, these nanostructures can be generated in UV and heat treatment after molding. In other aspects, the glass composition can exhibit photochromic properties. In further aspects, the glass compositions disclosed herein may include one or more rare earth metal compounds. Again, without wishing to be bound by any theory, it is believed that the inclusion of rare earth metals may further provide photoluminescent properties to the glass compositions disclosed herein. Such properties may be utilized in certain aspects to produce laser host materials if desired. In further aspects, the glass compositions are photoluminescent. In certain aspects, the one or more rare earth metal ions are present in an amount up to about 10 mol%, including exemplary values of about 0.01 mol%, about 0.05 mol%, about 0.1 mol%, about 0.5 mol%, about 1 mol%, about 1.5 mol%, about 2 mol%, about 2.5 mol%, about 3 mol%, about 3.5 mol%, about 4 mol%, about 4.5 mol%, about 5 mol%, about 5.5 mol%, about 6 mol%, about 6.5 mol%, about 7 mol%, about 7.5 mol%, about 8 mol%, about 8.5 mol%, about 9 mol%, and about 9.5 mol%. Embodiments of our glass compositions can provide glasses that have been observed to resist crystallization, thus allowing for the formation of various articles by any method known in the art, such as, but not limited to: down drawing (by a slot draw process or a fusion draw process), fiber drawing, float processing, or thin rolling of the glass. In other aspects, the method can include forming the glass into any desired shape. Various forming methods can also be used, such as casting, molding, pressing, rolling, float, etc. In other aspects, the articles disclosed herein can be formed by a float / flat glass pressing process, a press-blowing process, a blow-blowing process, or any combination thereof. In other aspects, the method can also include glass blowing, hot casting, flame processing, kiln casting, and / or kiln forming. It should also be understood that other low temperature glass manufacturing methods can also be utilized. For example, but not limited to, a glass wheel forming method can also be considered. In additional aspects, the glass compositions disclosed herein are substantially free of carbonates. However, it should be understood that the batch materials used to form the glass compositions disclosed herein may contain some amounts of carbonates. In another aspect, the glass compositions disclosed herein exhibit a relative humidity greater than about 80×10 -7 K -1 , greater than about 90×10 -7 K -1 , greater than about 100×10 -7 K -1 , greater than about 110×10 -7 K -1 , greater than about 120×10 -7 K -1 , greater than about 130×10 -7 K -1 , greater than or equal to approximately 140×10 -7K -1 The linear temperature expansion coefficient. It will be appreciated that in some aspects, the mechanical forming methods of the glass compositions disclosed herein will need to be adjusted for lower temperature processing ranges and reduced radiative heat flux losses. In some aspects, additional cooling may be required during the glass transition. In other aspects, however, longer annealing cycles may be used. In other aspects, the Vickers hardness of the glasses disclosed herein depends on the applied load. In some aspects, under certain loads (as shown in the examples below), the glass compositions disclosed herein can exhibit a Vickers hardness substantially equal to or less than that of conventional soda-lime glass compositions. In further aspects, any of the glass compositions disclosed herein can exhibit crack resistance that is greater than the crack resistance of conventional soda-lime glass compositions. Surprisingly, it was found that the glass compositions disclosed herein have significantly higher crack resistance (CR) than conventional soda-lime glass. Crack resistance is defined as the force at which the probability of a corner crack in Vickers indentation is 50%, and can be considered as the resistance of a material to crack initiation. It is a particularly important mechanical property for glass because it can be used to characterize the damage resistance of the glass. In further aspects, the glass compositions disclosed herein can exhibit a crack resistance of greater than about 0.1 kgf, greater than about 0.2 kgf, greater than about 0.3 kgf, greater than about 0.4 kgf, greater than about 0.5 kgf, greater than about 0.6 kgf, greater than about 0.7 kgf, greater than about 0.8 kgf, greater than about 0.9 kgf, or even greater than about 1.0 kgf. Products In certain aspects, disclosed herein are articles comprising any of the compositions disclosed above. For example, but not limited to, disclosed herein are articles comprising a glass composition comprising: about 25 to about 55 mol% P2O5; about 5 to about 45 mol% SiO2; about 5 to about 22 mol% Al2O3; about 5 to about 30 mol% ZnO; greater than 0 to about 20 mol% of the total amount of Na2O, K2O, and / or Li2O; about 2 to about 8 mol% CaO; and / or about 2 to about 8 mol% MgO. In further aspects, any of the additional elements disclosed above can be present in the glass compositions used to form the articles disclosed herein. In certain aspects and as disclosed herein, depending on the amount of iron oxide present in the compositions disclosed herein, the article can be transparent or translucent, depending on the desired application. In other aspects and as disclosed above, the article can also be photoluminescent. It should also be understood that other ions and elements can also affect the translucency of the article. For example, translucency can be obtained by any additive disclosed above, including but not limited to, for example, by adding tin oxide. In other aspects, the article may include any article known in the art requiring the mechanical properties, chemical properties, and optical properties disclosed herein. In other aspects, the article disclosed herein may include hollow vessels, tableware, containers, plates, sheets (including sheets prepared by a float process), cookware, powders, fibers, cones, spheres, blades, or any combination thereof. In other aspects, the article may include tableware, tableware, cookware, plate glass, windows, windshields, hollow vessels, jars, art and craft glass objects, laser matrix materials, optical fibers, hollow fibers, tubular fibers, containers for laboratory use, or any combination thereof. In other aspects, articles can be formed to meet technical requirements (high chemical resistance and durability, mechanical strength, combined with low melting point, etc.) as well as artistic expression and aesthetic appearance. For example and without limitation, the color of the article can be controlled by varying the amount of iron oxide and / or the amount of one or more other transition oxides to form a desired article. Again, for example and without limitation, an article can be formed with a darker color. In these aspects, the articles can include colored bottles (wine bottles, beer bottles, etc.), colored medicine bottles / ampoules (to protect light-sensitive drugs), sunglass lenses, works of art or crafts, etc. In other aspects, the articles disclosed herein can be formed by any process. For example, the articles can be formed by a float or flat press process, a press-blow process, a fiber drawing process, a blow-blow process, or any combination thereof. However, in other aspects disclosed herein, the articles can also be used in a variety of electronic devices or portable computing devices, light diffusers, automobiles, appliances, medical industries, food industries, and even architectural applications. In other aspects, the articles disclosed herein can have any shape or configuration known in the art. method Also disclosed herein are methods of making the disclosed compositions and disclosed articles. In certain aspects, disclosed herein is a method comprising: a) providing: about 25 to about 55 mol% of P2O5; about 5 mol% to about 45 mol% of SiO2; about 5 mol% to about 22 mol% of Al2O3; about 5 mol% to about 30 mol% of ZnO; a total amount of Na2O, K2O, and / or Li2O greater than 0 mol% to about 20 mol%; about 2 mol% to about 8 mol% of CaO; and / or about 2 mol% to about 8 mol% of MgO; b) forming a homogeneous mixture; c) melting the mixture at a temperature of about 1000°C to about 1300°C; and cooling the composition to form a glass composition. In further aspects, the glass composition is any of the glass compositions disclosed above.In further aspects, the mixture can be melted at a temperature of about 1000°C to about 1300°C, including exemplary values of about 1050°C, about 1100°C, about 1150°C, about 1200°C, and about 1250°C. In further aspects, any of the above disclosed components and elements may also be present in the mixture prior to melting. In further aspects, a plurality of nanoparticles can be formed during the melting and cooling process and present in the cooled article. In additional aspects, the method can further comprise forming any of the articles disclosed above. In other aspects, the glass composition can exhibit any of the above disclosed features and properties. In these exemplary aspects, these compositions can be transparent, translucent or opaque (depending on the specific percentage of each component), and have any of the above disclosed color characteristics. In further aspects, embodiments of the methods of forming the glass compositions disclosed herein can provide a reduction in CO2 emissions of at least about 25%, at least about 30%, at least about 35%, at least about 40%, at least about 45%, or at least about 50% compared to a reference method of making a conventional soda-lime glass composition. In some embodiments, this reduction in CO2 can be provided by a lower melting point of the composition.
[0122] In additional aspects, the methods disclosed herein can require at least about 30% less, at least about 35% less, at least about 40% less, at least about 45% less, or at least about 50% less British Thermal Units (BTUs) compared to conventional methods for making conventional soda-lime glass compositions.
[0123] In some further aspects, the methods disclosed herein include the step of forming a glass article. Any method of forming or shaping an article known in the art can be used. For example, but not limited to, the method of forming a glass article disclosed herein may include down-drawing of glass (by slot drawing or fusion drawing), fiber drawing, float processing or thin rolling. In other aspects, the method may include forming the glass into any desired shape. Various forming methods may also be used, such as casting, molding, pressing, rolling, drawing, float, etc. In other aspects, the articles disclosed herein may be formed by float / flat glass pressing process, press-blowing process, blow-blowing process or any combination thereof. In yet other aspects, the method may also include glass blowing, hot casting, flame processing, kiln casting and / or kiln forming. It should also be understood that other low-temperature glass manufacturing methods may also be used. For example, but not limited to, glass wheel forming methods may also be considered. Example The following examples are presented to provide those of ordinary skill in the art with a complete disclosure and description of how to prepare and evaluate the compounds, compositions, articles, devices and / or methods claimed herein, and are intended to be purely exemplary and not intended to limit the present disclosure. Efforts have been made to ensure accuracy with respect to numbers (e.g., amounts, temperature, etc.), but some errors and deviations should be accounted for. Example 1 Table 1 shows comparative properties of an exemplary article formed according to one aspect of the present invention and a soda-lime-silicate article. Table 1. Comparison of properties of articles formed from a soda-lime-silicate reference composition and an exemplary composition disclosed herein in one aspect (LG2-CaMgZn in Table 9). Example 2 Figure 3 and Figure 4 And Table 2 below is a table showing exemplary and non-limiting glass compositions formed according to the present disclosure. Table 2. Composition (mol %) of various glasses according to aspects of the present disclosure. The probability of crack initiation (PCI) of some exemplary embodiments shown in Table 2 was evaluated. Figure 5 The PCI is shown as a function of loading for a glass having a composition of an exemplary embodiment of the glass composition labeled "Glass 1" in Table 2 and a conventional soda-lime glass (SLS). A series of photographs were taken during the experimental work to evaluate how the glass withstands the load. Figure 6Included are multiple images showing the indentations formed in images (a), (b), and (c) in a glass having the composition of an exemplary embodiment of the glass composition labeled "Glass 1" in Table 2 and the indentations formed in conventional soda-lime glass in images (a), (b), and (c). Figure 6 The dents formed in images (d), (e), and (f). Figure 6 The load applied in images (a) and (d) is 1 kgf. Figure 6 The load applied in images (b) and (e) is 0.5 kgf. Figure 6 The load applied in images (c) and (f) is 0.1 kgf. The tests performed show that exemplary embodiments of the glass composition can be used to produce glass having the ability to avoid breakage and withstand much greater loads. Table 3 shows glass compositions according to aspects of the present disclosure and reference soda-lime-silicate glass compositions as disclosed in Ashby, MF Material profiles. In Materials and the Environment, 2nd ed.; Elsevier, 2013, pp. 459-595 (in mol. %). Table 3. Compositions of various glasses according to aspects of the present disclosure and comparative soda-lime-silicate compositions (mol %). Table 4 shows the glass transition temperatures (T) of exemplary glass compositions annealed at 700 K for one hour at four uniformly distributed slow heating rates according to one aspect of the present invention. g ) (These values were calculated by using TransitionPy software). Figure 1 The absorption spectrum of a glass composition according to one aspect in the wavelength range of 300-850 nm is shown. Table 4. Glass transition temperature as a function of heating rate ( Figure 3 Glass in 1) Table 5 shows the thermal properties of glass 1, measured by DSC at a heating rate of 10 K min and subsequently analyzed using TransitionPy software. These values are compared with those found in the colorimetric glass transition of soda-lime silicate glasses by Mancini, M., Sendova, M. and Mauro, J. C. geometric analysis and brittleness using constant cooling rate cycles. JACerS [Online] 2021, 3, 348-357. http: / / ceramics.onlinelibrary.wiley.com / doi / 10.1111 / ijag.16073 and Henneberry, B. Thomas. All about soda-lime glass - composition and properties. https: / / www.thomasnet.com / articles / plant-faci li ty-equipment / soda-lime-glass / #table. The contents of which are hereby incorporated in their entirety into this article. Table 5. Comparison of exemplary glass compositions of one aspect with soda-lime-silicate glass. ( Figure 3 Glass in 1) Example 3 Figures 2A-2D The relaxation characteristics of a glass composition according to one aspect are shown. In these exemplary curves, the glass was melted at 1.5×Tg, quenched to room temperature at 10°C / min, and then reheated to 0.9×Tg and held for one hour to allow relaxation. The tensile parameter β evolves as Figure 2A shown. Figure 2B The viscosity evolution is shown in Figure 2C middle. Figure 2D The simulated thermal history is shown. Example 4 Various glass compositions were evaluated to measure their coefficient of linear temperature expansion (CTE) and the results are shown in Table 6. Table 6 CTE of various glasses, unit is ×10 -7 (K -1 ). Example 5 The hardness of the glasses disclosed herein was further evaluated and the results are shown in Table 7. Table 7 Vickers indentation hardness of various glasses, unit: kgf / mm 2 . Example 6 The glass compositions disclosed herein have shown surprisingly excellent crack resistance. Some glass compositions (as shown in Table 9) have such great crack resistance that the glass will not break under an applied load of 1 kgf. It was found that the force was not high enough to produce 50% cracks. The data show that the crack resistance of these glasses exceeds 10 times that of standard soda-lime glass. Without wishing to be bound by any theory, it is hypothesized that the total ZnO content may play an important role in increasing the crack resistance. The measured crack resistance of the exemplary glasses is shown in Table 8. Table 8. Crack resistance Example 7 Table 9 shows exemplary and non-limiting glass compositions formed according to the present disclosure. Tables 10-14 show durability, hardness, coefficient of thermal expansion (CTE) measurement data, elastic properties, and Tg data for various exemplary embodiments of the exemplary glass compositions identified in Table 9. Table 9. Compositions of various glasses according to aspects of the present disclosure. (mol %) Table 10 Durability Table 11 Hardness Table 12 CTE measurement (×10 -7 )(50-300℃) Table 13 Elastic properties Table 14Tg When a large amount of stress is generated during cooling, thermal shock occurs and causes the glass to crack. If the glass has a high coefficient of expansion, a high Young's modulus, and / or a high glass transition temperature, greater stress will be generated during cooling. The exemplary compositions identified in Table 9 have a significantly lower coefficient of thermal expansion than most soda-lime glasses, while also having a low Young's modulus and a low glass transition temperature. These embodiments can also exhibit higher thermal shock resistance than most soda-lime glasses. The durability of the various exemplary glass compositions listed in Table 9 was tested, and the results of such testing are shown in Table 10, which shows that the durability of the exemplary compositions of Table 9 is very good and comparable to, if not better than, conventional soda lime glass. The numbers in Table 10 above are the concentrations of each element present in solution after exposure of the same particle size and total surface area of glass to 62 mL of RO water at 75°C for 2 days in a sealed reaction vessel. Therefore, glasses with higher durability have lower concentrations of dissolved ions in solution. The surface area of some less durable glasses may have changed during testing, so the results are not normalized by surface area. Some of the glasses tested had such low durability that they deteriorated in air and were not tested. This most often occurs when the phosphorus exceeds 45 mol% and the alumina content is low, and / or if the zinc content is high. In general, the tests conducted showed that CaO can greatly improve durability. Replacing CaO with MgO reduced durability, and replacing CaO with ZnO reduced durability or even exceeded MgO. We believe that small additions of alkali metal oxides in place of MgO or ZnO may provide enhanced durability without compromising crack resistance, which may be traded off with durability. Crack resistance can depend on the modifiers used for the exemplary glass compositions tested as identified in Table 9. Exceptionally high crack resistance (1 kgf or higher) can be obtained in compositions with reduced ZnO (e.g., low ZnO) or without ZnO. For different embodiments, removing or reducing ZnO can provide some advantages because ZnO can reduce durability relative to using CaO and MgO, and is also one of the more expensive batch materials. Some ZnO can still be used to obtain other desired properties (e.g., high UV absorption). However, the tests conducted show that avoiding or reducing ZnO can make the glass have high crack resistance. Stones are another word for unmelted particles in the glass, and their presence usually indicates that higher temperatures or longer melting times are required to form the glass. For example, stones can be unmelted silica particles that have clump together. The composition of the glass can be adjusted to reduce stones by reducing the Al2O3 content, increasing the P2O5 content, and / or reducing the SiO2 content. It was found that calcining the raw material batch at at least 300°C helped improve the melt quality of the glasses subsequently formed in some of the experiments performed, as reflected in Tables 9 - 14. It was found that the alumina content strongly controlled the stone and melt quality, with differences of up to 0.25 mol% Al2O3 making the difference between high quality glass and glass with many stones when melted at the same temperature. Additional testing was performed on other glass compositions that demonstrate embodiments of the glass compositions of the present invention that can be prepared and used in glass articles. Tables 15 and 16 below provide composition information for these additional exemplary embodiments. The compositions in Table 16 are compositions after the glass raw materials are melted to form the glass. The compositions listed in Table 15 are compositions of the materials pre-melted to form the glass. Table 15 Compositions of various exemplary glass compositions (mol%) Table 16 Compositions (mol%) of various exemplary glass compositions Sample <![CDATA[SiO2]]> <![CDATA[P2O5]]> <![CDATA[Al2O3]]> CaO MgO ZnO <![CDATA[Na2O]]> <![CDATA[K2O]]> LG2-Ca.65 9.8 39.7 4.0 25.2 3.20 8.2 8.5 1.3 LG2-Ca.71 9.5 39.8 3.8 24.7 12.0 0.04 8.8 1.26 LG2-Ca.72 9.55 39.5 3.8 24.7 6.3 5.5 9.2 1.3 LG2-Ca.6 9.6 40.3 3.34 25.7 3.1 8.17 8.56 1.25 LG2-Ca.6Na 9.5 39.88 5.36 35.98 0.33 0.1 8.8 0.064 LG2-Ca.6NZ 9.6 40 5.49 26.6 0.29 9.2 8.7 0.046 LG2-Ca.6NZM 9.7 40 4.38 25.7 3.25 8.2 8.5 0.15 LG2-Ca.61 9.7 39.8 3.62 23.7 3.1 8.2 8.47 3.3 LG2-Ca.5 9.5 40.02 4.96 45 0.07 0.14 0.06 0.14 LG2-Ca.6KZ 9.5 39.8 5.96 26.8 0.25 9.1 0.20 8.25 Our experimental work on the compositions of Tables 15 and 16 shows that some compositions of glasses made from glassmaking materials may be slightly different based on contamination that may occur in the container or furnace in which the glass may be melted and formed. Due to these factors, the melt composition may be slightly different from the pre-melt composition, depending on how the glass is prepared. For example, in the compositions of Table 16, the composition was melted in a crucible made of Al2O3, and the presence of this alumina slightly changed the pre-melt composition (the decrease in P2O5 may be due to volatilization from the melting process and the increase in Al2O3). Figure 7 is a graph showing how the coefficient of thermal expansion (CTE) of several exemplary embodiments of the glass compositions included in Table 16 varies as a function of temperature compared to conventional soda lime glass (SLS). Figure 7 As can be appreciated, embodiments of the glass compositions can be used to form glass that can have significantly lower CTE values over a wide range of temperatures compared to conventional soda lime glass (SLS). A single pass flow (SPFT) evaluation was also performed in the experimental work to compare different exemplary embodiments of soda lime glass (SLS) and glass compositions. It is expected that the dissolution rate of a given glass component is inversely proportional to the concentration of the component in the solution, for example, the dissolution rate of sodium from the glass will decrease with the increase of the sodium content in the solution, as well as through the so-called "reverse reaction". SPFT is a dynamic durability technique that measures the release rate of different components of the glass at several solution flow rates. These different flow rates produce different background concentrations of the substance of interest in the reaction vessel. The relationship between the flow rate and the dissolution rate is used to calculate what the dissolution rate will be in the case of zero background concentration, that is, in the absence of the influence of the reverse reaction or background concentration. This dissolution rate, called the forward dissolution rate, is an estimate of the release rate of each component of the glass when the glass is in contact with a fresh solution, and is one of the most direct methods for comparing the durability of different glass compositions. The forward dissolution rate is further normalized by the composition of the glass to allow direct comparison of different compositions, that is, without normalization, it is expected that a glass with twice the Na2O will show twice the Na released into the solution while effectively having the same durability. Additional information on SPFT can be found in ASTM C1662-10. Table 17 below provides the results of this evaluation work. The elements Al, Ca, K, Mg, Na, P, Si and Zn in Table 17 identify the different elements in the glass composition and how these elements were found to dissolve during the testing. The forward dissolution rate is given in grams per square meter per day. The tests were conducted in RO water at 50°C. Glass frit with an average particle size of 362.5 microns (-300, +425 micron mesh) was used in the experiments. Using the geometric surface area method, each container contained approximately 1.38×10 -7 m 2The influent solution was buffered to pH 7.5 using Tris-HCl to eliminate the effect of pH changes on the dissolution measurements. The forward dissolution rates for different glass compositions typically span many orders of magnitude, with a strong dependence on the solution environment. To illustrate this comparison, Table 17 includes forward dissolution rates for soda lime glass (taken from M. Fournier et al. / Journal of Nuclear Materials 476 (2016) 140e154) and borosilicate glass (taken from Neeway, J, Will iams, B, Asmussen, R, Leavy, I, Parruzot, B, Stephenson, J, Cordova, E, & McElroy, E (2017)). FY2016 ILAW Glass Corros ion Testing with the Single-Pas s Flow-Through Method (available from https: / / www.pnnl.gov / main / publications / external / technical_reports / PN NL-26169.pdf) under different conditions. Under the same conditions, the results of this experimental work indicate that the example glass compositions have durability that is quite suitable for commercial applications (e.g., the durability does not exceed the durability that can be observed under other types of conditions). Table 17 SPFT evaluation results Experiments conducted have shown that the glass composition may include about 1.5 mol% (mol%) aluminum oxide (Al2O3) to 5 mol% Al2O3 and 5 mol% silicon dioxide (SiO2) to 45 mol% SiO2 to provide surprising results. For example, the glass composition may include 1.5 mol% Al2O3 to 4 mol% Al2O3, or may include 2 mol% Al2O3 to 3.6 mol% Al2O3, or may include 2.8 mol% Al2O3 to 3.3 mol% Al2O3. In such exemplary embodiments, the silicon dioxide content may be in a range between 5 mol% silicon dioxide (SiO2) and 15 mol% SiO2 (e.g., between 5 mol% SiO2 and 10 mol% SiO2, between 5 mol% SiO2 and 12 mol% SiO2, or between 7 mol% SiO2 and 15 mol% SiO2, etc.). As can be understood from the above, embodiments of the glass composition may also include other components that may promote one or more desired properties of the glass or articles formed from the glass. For example, the glass composition may also include phosphorus pentoxide (P2O5). By using phosphate compounds, phosphorus pentoxide may be added to the glass composition for forming a glass having the glass composition. For example, monosodium phosphate, monocalcium phosphate, aluminum metaphosphate, and / or dimagnesium phosphate may be added to the glass raw materials used to form the glass so that the glass has a glass composition containing a desired content of P2O5 (e.g., a content of P2O5 within a preselected composition range of P2O5 or at a preselected P2O5 content). The use of these types of phosphate compounds may allow the formation of glass without the use of carbonate modifiers (e.g., CaCO3, Na2CO3, etc.) to help reduce the direct carbon footprint of the raw materials used to manufacture glass having a preselected desired glass composition. In some embodiments, the glass composition may include less than 55 mol % P2O5 and greater than 35 mol % P2O5. For example, the glass composition may include a P2O5 content of 38 mol% P2O5 to 50 mol% P2O5 or a P2O5 content of 40 mol% P2O5 to 45 mol% P2O5. The experiments conducted also show that embodiments of the glass composition may include other components to help provide the glass with desired properties. For example, embodiments of the glass composition may also include one or more modifiers (e.g., alkali metal modifiers and alkaline earth metal modifiers). In some embodiments, the glass composition may include a total modifier content of 40 mol % to 47 mol % (e.g., the total content of all of these modifiers included in the glass composition may be in the range of 40 mol % to 47 mol %). In other embodiments, the glass composition may include a total modifier content in the range of 30 mol % to 40 mol % or about 35 mol % (e.g., the total content of all of these modifiers included in the glass composition may be in the range of 30 mol % to 40 mol %, or between 33 mol % and 37 mol %, etc.). For example, one or more modifiers may be included in a glass composition to help provide one or more properties to the glass composition, which may help the glass be more effectively used to make a particular type of article. For example, CaO and / or KO may be used as modifiers to help improve the durability of a glass having the glass composition. For example, a glass composition that may have a relatively low Al2O3 content may have a higher CaO content and / or a higher KO content. In some embodiments, the CaO content of the glass composition may be greater than or equal to 22 mol% CaO (and not more than 47 mol% CaO or not more than 40 mol% CaO). In some embodiments, K2O can be less than or equal to 10 mol% in the glass composition. Within such a range, the glass can be transparent (eg, avoiding opacity), and we have found that this type of composition range can help avoid phase separation. In some embodiments, Na2O may preferably not exceed 20 mol% of the glass composition. We have found that Na2O levels exceeding 20 mol% may cause the glass to be opaque and / or may degrade under ambient conditions in some cases. MgO, ZnO and / or CaO may be used in the glass composition to help provide a transparent and durable glass. For example, the inclusion of CaO may help increase the Vickers hardness of a glass having the glass composition. We have found that glass compositions that do not contain divalents often result in opaque glass or glass that degrades in air or ambient conditions, so many preferred embodiments may include one or more divalent modifiers. We have also found that modifiers with relatively high field strengths (e.g., Na2O, MgO, and ZnO) can help provide high crack resistance to glasses having the glass composition. In contrast, the inclusion of CaO and / or K2O can reduce the crack resistance of the glass composition. For embodiments of glass compositions requiring high crack resistance, the glass composition can preferably have about 10 mol% CaO (e.g., 8 mol% CaO to 12 mol% CaO), and 15 mol% to 30 mol% ZnO and / or MgO (e.g., the content of ZnO and MgO can be between 15 mol% and 30 mol% in total). Modifiers may be selected to aid in coloration and other qualities. For example, in some embodiments, the alkali metal content of the glass composition may not exceed 14 mol % alkali metal to help avoid phase separation and avoid the glass being blue (e.g., sky blue) or white in color. In some embodiments, having an alkali metal content of about 10 mol % may allow the glass to be compatible with a variety of different resistance melting techniques used to make the glass. Examples of alkali metal modifiers include Na2O and K2O. Iron oxide (Fe2O3) can be used as a modifier in relatively small amounts to help improve durability and increase liquidus viscosity without adversely affecting the transparency of the formed glass or the processability of the glass. Some embodiments of the glass composition can include greater than 0 mol % Fe2O3 and less than 0.5 mol % Fe2O3. The addition of ZnO and MgO has a similar effect on the properties of glasses having this glass composition. Both modifiers can be used to help improve crack resistance, but can provide this crack resistance at the expense of durability (e.g., durability may be reduced while still sufficient to meet a particular set of design goals, while crack resistance may be increased). A higher alkali metal modifier content and a lower alkaline earth metal modifier content can provide a glass with a higher coefficient of thermal expansion compared to a glass with a lower alkali metal modifier content and a higher alkaline earth metal modifier content. The combination of modifiers for a particular application can be modified within the above content ranges to provide a desired glass composition for a glass article that can have a desired coefficient of thermal expansion for a particular application (e.g., for forming a particular type of article). In some embodiments, the glass composition including the modifier and P2O5 can have between 9 mol% and 10 mol% SiO2 (e.g., 9.4-9.5 mol% SiO2), 40 mol% to 42 mol% P2O5 (e.g., 41.5-42 mol% P2O5), 2.8 mol% to 3.2 mol% Al2O3 (e.g., 2.85-3 mol% Al2O3, 24.5 mol% to 26 mol% CaO (e.g., 24.7-25.3 mol% CaO), 2.7 mol% to 3.0 mol% MgO (e.g., 2.8-2.9 mol% MgO), 8.4 mol% to 8.7 mol% ZnO (e.g., 8.5-8.8 mol % ZnO), 8.2 mol % to 8.8 mol % Na2O (e.g., 8.4-8.6 mol % Na2O), and 1.0 mol % to 1.3 mol % K2O (e.g., 1.08-1.2 mol % K2O). As another example, an embodiment of the glass composition may include 9.46 mol % SiO2, 41.76 mol % P2O5, 2.89 mol % Al2O3, 24.90 mol % CaO, 2.83 mol % MgO, 8.52 mol % ZnO, 8.51 mol % Na2O, and 1.13 mol % K2O. As yet another example, an embodiment of a glass composition including a modifier may have 8-11 mol% SiO2, 40-43 mol% P2O5, 1.5-3 mol% Al2O3, 20-50 mol% modifier, wherein the modifier may include a combination of CaO, MgO, ZnO, Na2O, and / or KO. As yet another example, an embodiment of a glass composition including a modifier may have 7-12 mol% SiO2, 40-45 mol% P2O5, 1.5 mol%-4 mol% Al2O3, 30-50 mol% modifier, wherein the modifier includes one or more of: CaO, MgO, ZnO, Na2O, and / or KO. As yet another example, an embodiment of a glass composition including a modifier may have 9-10 mol% SiO2, 39-43 mol% P2O5, 1-4 mol% Al2O3, and 43-51 mol% other ingredients. Other components may include CaO, MgO, Na2O and / or K2O. Other embodiments of the glass composition may have 9 mol % to 10 mol % SiO 2,%, 40 mol% to 42 mol% P2O5, 2 mol% to 4 mol% Al2O3, 20 mol% to 26 mol% CaO (e.g., 24.7-25.3 mol% CaO), 2 mol% to 6.0 mol% MgO (e.g., 2.8-2.9 mol% MgO), 0 mol% to 9 mol% ZnO, 0 mol% to 9 mol% Na2O, and 0 mol% to 1.5 mol% KO. As yet another example, the glass composition can have 8 mol% to 11 mol% SiO2, 38 mol% to 42 mol% P2O5, 1 mol% to 4 mol% Al2O3, 15 mol% to 30 mol% CaO, and 15 mol% to 30 mol% MgO. Some such embodiments can also include 5 mol% to 10 mol% Na2O and 1.0 mol% to 1.5 mol% KO. As yet another example, the glass composition can have 7 mol%-13 mol% SiO2, 38 mol%-44 mol% P2O5, 1.5 mol%-4 mol% Al2O3, 15 mol%-30 mol% CaO, 15 mol%-30 mol% MgO, and no more than 5 mol% ZnO (e.g., 0-5 mol% ZnO, less than 3 mol% ZnO, and greater than 0 mol% ZnO, etc.). As yet another example, embodiments of the glass composition may have 9-10 mol% SiO2, 41-42 mol% P2O5, 2.5-3.8 mol% Al2O3, 20-30 mol% CaO, 2-30 mol% MgO, 0-10 mol% ZnO, 0-9 mol% Na2O, and 0-1.5 mol% K2O. As yet another example, embodiments of the glass composition may have 9-10 mol% SiO2, 39-43 mol% P2O5, 1 mol%-4 mol% Al2O3, 15-30 mol% CaO, 0-30 mol% MgO, 0-10 mol% ZnO, 0-10 mol% Na2O, and 0-1.5 mol% K2O. For example, embodiments of glass compositions including modifiers may have 9-10 mol% SiO2, 39.0-42.5 mol% P2O5, 2.0-4.0 mol% Al2O3, 20-27 mol% CaO, 6-30 mol% MgO, 0.5-5 mol% ZnO, 0.5-9 mol% Na2O, and 0.5-1.5 mol% K2O. As yet another example, embodiments of glass compositions including modifiers may have 8-12 mol% SiO2, 39.0-42.5 mol% P2O5, 2.0 mol%-4.0 mol% Al2O3, 20-27 mol% CaO, 6-30 mol% MgO, 0.5-5 mol% ZnO, 0.5-9 mol% Na2O, and 0.5-1.5 mol% K2O. As yet another example, an embodiment of a glass composition including a modifier may have 8-12 mol % SiO2, 39-43 mol % P2O5, 1-4 mol % Al2O3, 5-25 mol % CaO, 5-30 mol % MgO, 4-8 mol % Na2O, and 0.5-1.5 mol % K2O, and 0-0.5 mol % Fe2O3. Embodiments of the glass compositions may also include additional modifiers (eg, Li2O, etc.) and / or colorants. In view of the described methods and compositions, certain more specifically described aspects of the invention are described below. However, these specifically described aspects should not be interpreted as having any limiting effect on any different claims containing different or more general teachings described herein, or that the "particular" aspects are limited in some way other than the inherent meaning of the language and formulation used literally herein. aspect: Aspect 1: A glass composition comprising: about 25 to about 55 mol% P2O5; about 5 to about 45 mol% SiO2; about 5 to about 22 mol% Al2O3; about 5 to about 30 mol% ZnO; a total amount of Na2O, K2O and / or Li2O greater than 0 to about 20 mol%; about 2 to about 8 mol% CaO and / or about 2 to about 8 mol% MgO. Aspect 2: The glass composition of Aspect 1, wherein the glass composition exhibits a melting point at least about 150°C lower than the melting point of a conventional soda-lime-silicate glass composition. Aspect 3: The glass composition of Aspect 1 or 2, wherein the glass composition exhibits a melting point at least about 250° C. lower than the melting point of a conventional soda-lime-silicate glass composition. Aspect 4: The glass composition of any of aspects 1-3, wherein the glass composition exhibits a melting point less than about 1,400°C. Aspect 5: The glass composition according to any one of aspects 1-4, further comprising Fe2O3 in an amount of up to about 10 mol%. Aspect 6: The glass composition of Aspect 5, wherein when Fe2O3 is present at up to 0.5 mol%, the glass composition is substantially colorless. Aspect 7: The glass composition according to aspect 6, wherein the composition exhibits a wavelength of less than or equal to about 0.49 cm in the visible light range of about 400 nm to about 800 nm. -1 The average absorption coefficient. Aspect 8: The glass composition of Aspect 6 or 7, wherein the glass composition exhibits a percent transmittance greater than about 80% in a wavelength range of about 400 nm to about 800 nm. Aspect 9: The glass composition of Aspect 5, wherein when Fe2O3 is present in an amount of about 0.5 mol% to about 5 mol%, the glass composition is translucent gray. Aspect 10: The glass composition according to any of aspects 1-5, further comprising one or more transition metal oxides, wherein the transition metal oxide comprises an oxide of copper, nickel, cobalt, chromium, silver, tin, or any combination thereof. Aspect 11: The glass composition of aspect 10, wherein the one or more transition metal oxides are present in an amount of up to about 2 mol%. Aspect 12: The glass composition according to aspect 11, wherein the glass composition is translucent. Aspect 13: The glass composition according to aspect 11 or 12, wherein the glass composition exhibits a percent transmittance of less than about 85% in a wavelength range of about 400 nm to about 800 nm. Aspect 14: The glass composition of any of aspects 10-13, wherein the glass composition comprises a plurality of nanoparticles. Aspect 15: The glass composition of any of aspects 1-14, wherein the glass composition comprises one or more rare earth metal ions. Aspect 16: The glass composition of aspect 15, wherein the one or more rare earth metal ions are present in an amount of up to about 10 mol%. Aspect 17: The glass composition of Aspect 15 or 16, wherein the glass composition is photoluminescent. Aspect 18: The glass composition of any of aspects 1-17, wherein the composition exhibits a difference between a crystallization temperature and a glass transition temperature of greater than about 100°C when measured at room temperature and ambient pressure. Aspect 19: The glass composition of any of aspects 1-18, wherein the glass composition is substantially free of carbonates. Aspect 20: The glass composition according to any one of aspects 1-19, wherein the glass composition exhibits a relative humidity greater than about 100×10 -7 K -1 The linear temperature expansion coefficient. Aspect 21: The glass composition of any of aspects 1-20, wherein the glass composition exhibits a crack resistance greater than about 0.1 kgf. Aspect 22: The glass composition of any of Aspects 1-21, wherein the glass composition exhibits a crack resistance greater than about 0.3 kgf. Aspect 23: The glass composition of any of aspects 1-22, wherein the glass composition exhibits a crack resistance greater than about 0.6 kgf. Aspect 24: The glass composition of any of Aspects 1-23, wherein the glass composition exhibits a crack resistance greater than about 1.0 kgf. Aspect 25: An article comprising the glass composition according to any one of aspects 1-24. Aspect 26: The article of Aspect 25, comprising tableware, cutlery, cookware, plate glass, windows, windshields, hollow vessels, jars, arts and crafts glass objects, laser-based materials, optical fibers, hollow fibers, laboratory-usable containers, or any combination thereof. Aspect 27: A glass article comprising a glass composition, the glass composition comprising about 25-55 mol% P2O5; about 5 to about 45 mol% SiO2; about 5 to about 22 mol% Al2O3; about 5 to about 30 mol% ZnO; a total amount of Na2O, K2O and / or Li2O greater than 0 to about 20 mol%; about 2 to about 8 mol% CaO and / or about 2 to about 8 mol% MgO. Aspect 28: The article of Aspect 27, wherein the glass composition exhibits a melting point at least about 150°C lower than the melting point of a conventional soda-lime-silicate glass composition. Aspect 29: The article of Aspect 27 or 28, wherein the glass composition exhibits a melting point at least about 250°C lower than the melting point of a conventional soda-lime-silicate glass composition. Aspect 30: The article of any of Aspects 27-29, wherein the glass composition exhibits a melting point of less than about 1,400°C. Aspect 31: The article of any of Aspects 27-30, wherein the glass composition further comprises Fe2O3 in an amount of up to about 10 mol%. Aspect 32: The article of Aspect 31, wherein when Fe2O3 is present at up to about 0.5 mol%, the article is substantially colorless. Aspect 33: The article of aspect 32, wherein the composition exhibits a wavelength of less than or equal to about 0.49 cm in the visible light range of about 400 to about 800 nm. -1 The average absorption coefficient. Aspect 34: The article of Aspect 32 or 33, wherein the article exhibits a percent transmittance greater than about 80% in the wavelength range of about 400 nm to about 800 nm. Aspect 35: The article of Aspect 34, wherein when the glass composition comprises Fe2O3 present in an amount of about 0.5 mol% to about 5 mol%, the article is translucent gray. Aspect 36: The article of any of Aspects 27-31, further comprising one or more transition metal oxides comprising oxides of copper, nickel, cobalt, chromium, silver, tin, or any combination thereof. Aspect 37: The article of Aspect 36, wherein the one or more transition metal oxides are present in the glass composition in an amount of up to about 2 mol%. Aspect 38: The article of Aspect 37, wherein the article is translucent. Aspect 39: The article of any of Aspects 37-38, wherein the article exhibits a percent transmittance of less than about 85% over a wavelength range of about 400 nm to about 800 nm. Aspect 40: The article of any of Aspects 36-39, wherein the glass composition comprises a plurality of nanoparticles. Aspect 41: The article of any of Aspects 27-40, wherein the glass composition comprises one or more rare earth metal ions. Aspect 42: The article of Aspect 41, wherein the one or more rare earth metal ions are present in an amount of up to about 10 mol%. Aspect 43: The article of any of Aspects 41 or 42, wherein the article exhibits photoluminescence. Aspect 44: The article of any of Aspects 27-43, wherein the glass composition exhibits a difference between a crystallization temperature and a glass transition temperature of greater than about 100°C when measured at room temperature and ambient pressure. Aspect 45: The article of any of Aspects 27-44, wherein the glass composition is substantially free of carbonates. Aspect 46: The article of any one of Aspects 27-45, wherein the glass composition exhibits a -7 K -1 The linear temperature expansion coefficient. Aspect 47: The article of any of Aspects 27-46, wherein the glass composition exhibits a crack resistance greater than about 0.1 kgf. Aspect 48: The article of any of Aspects 27-47, wherein the glass composition exhibits a crack resistance greater than about 0.3 kgf. Aspect 49: The article of any of Aspects 27-48, wherein the glass composition exhibits a crack resistance greater than about 0.6 kgf. Aspect 50: The article of any of Aspects 27-49, wherein the glass composition exhibits a crack resistance greater than about 1.0 kgf. Aspect 51: The article of any of Aspects 27-50, comprising tableware, cutlery, cookware, plate glass, windows, windshields, hollow vessels, jars, arts and crafts glass objects, laser-based materials, optical fibers, hollow fibers, tubular fibers, laboratory-usable containers, or any combination thereof. Aspect 52: A method comprising: a) providing: about 25 mol % to about 55 mol % P2O5; about 5 mol % to about 45 mol % SiO2; about 5 mol % to about 22 mol % Al2O3; about 5 mol % to about 30 mol % ZnO; a total amount of Na2O, K2O and / or Li2O greater than 0 mol % to about 20 mol %; about 2 mol % to about 8 mol % CaO and / or about 2 mol % to about 8 mol % MgO; b) forming a homogeneous mixture; c) melting the mixture at a temperature of about 1,000°C to about 1,300°C; and cooling the composition to form a glass composition as described in any of Aspects 1-26. Aspect 53: The method of aspect 52, further comprising forming an article comprising the glass composition. Aspect 54: The method of any of Aspects 52 or 53, wherein the method exhibits at least about 25% reduction in CO2 emissions compared to a reference method for making a conventional soda-lime glass composition. Aspect 55: The method of any of Aspects 52-54, wherein the method comprises requiring at least about btu as compared to a reference method for preparing a conventional soda-lime glass composition. Aspect 56. A glass composition comprising 35-50 mol % P2O5, 5-15 mol % SiO2, and 1.5-5 mol % Al2O3 (e.g., 38-45 mol % P2O5, 5-10 mol % SiO2, and 2.8-3.3 mol % Al2O3, or 40-45 mol % P2O5, 7-12 mol % SiO2, and 2.0-3.8 mol % Al2O3, or 2-4 mol % Al2O3). Aspect 57. The glass composition according to aspect 56, wherein 40-45 mol% P2O5 and 2-4 mol% Al2O3 are present. Aspect 58. The glass composition according to Aspect 56 or Aspect 57, further comprising 30-50 mol% of CaO, MgO, Na2O, K2O and ZnO in a total amount (e.g., 40-47 mol% or 35-45 mol%). Aspect 59. The glass composition of Aspect 56, Aspect 57 or Aspect 58, wherein K2O is less than or equal to 10 mol%. Aspect 60. The glass composition of Aspect 56, Aspect 57, Aspect 58 or Aspect 59, wherein Na2O is less than or equal to 20 mol% or less than or equal to 15 mol%. Aspect 61. The glass composition of Aspect 56, Aspect 57, Aspect 58, Aspect 59 or Aspect 60, wherein the CaO is at least 20 mol% or at least 22 mol% and is no more than 40 mol% CaO or no more than 30 mol% CaO. Aspect 62. A glass composition according to Aspect 56, Aspect 57, Aspect 58, Aspect 59, Aspect 60 or Aspect 61, wherein the glass composition also includes greater than 0 mol% Fe2O3 and no greater than 0.5 mol% Fe2O3, and / or has 0 mol% to 2 mol% iron oxide (e.g., Fe2O3 and FeO). Aspect 63. The glass composition of Aspect 56, Aspect 57, Aspect 58, Aspect 59, Aspect 60, Aspect 61 or Aspect 62, wherein the glass composition has a total amount of alkali metals of no more than 14 mol%. Method 64. A glass composition according to method 56, method 57, method 58, method 59, method 60, method 61, method 62 or method 63, wherein the total content of MgO and ZnO is greater than 0 mol% and not greater than 30 mol%. Aspect 65. A glass composition according to Aspect 56, Aspect 57, Aspect 58, Aspect 59, Aspect 60, Aspect 61, Aspect 62, Aspect 63 or Aspect 64, wherein the glass composition has no more than 9 mol% ZnO or has 0 mol% ZnO (e.g., between 0 mol% ZnO and 9 mol% ZnO, or wherein the glass composition is substantially free of ZnO). Aspect 66. The glass composition of Aspect 56, Aspect 57, Aspect 58, Aspect 59, Aspect 60, Aspect 61, Aspect 62, Aspect 63, Aspect 64, or Aspect 65, wherein the glass composition is substantially free of alkali metal oxides. Aspect 67. The glass composition of Aspect 56, Aspect 57, Aspect 58, Aspect 59, Aspect 60, Aspect 61, Aspect 62, Aspect 63, Aspect 64, or Aspect 65, wherein the glass composition has a total amount of alkali metal oxides of up to 10 mol%. Aspect 68. A glass composition according to Aspect 56, Aspect 57, Aspect 58, Aspect 59, Aspect 60, Aspect 61, Aspect 62, Aspect 63, Aspect 64, Aspect 65, Aspect 66 or Aspect 67, wherein the glass composition further comprises one or more transition metal oxides, wherein the transition metal oxides include oxides of copper, nickel, cobalt, chromium, silver, tin, or any combination thereof. Aspect 69. The glass composition of Aspect 56, Aspect 57, Aspect 58, Aspect 59, Aspect 60, Aspect 61, Aspect 62, Aspect 63, Aspect 64, Aspect 65, Aspect 66, Aspect 67 or Aspect 68, wherein the glass composition exhibits a melting point of less than about 1,300°C or less than about 1,200°C. Aspect 70. The glass composition of Aspect 56, Aspect 57, Aspect 58, Aspect 59, Aspect 60, Aspect 61, Aspect 62, Aspect 63, Aspect 64, Aspect 65, Aspect 66, Aspect 67, Aspect 68, or Aspect 69, wherein the glass composition exhibits a glass transition temperature of about 485°C to about 600°C. Aspect 71. The glass composition of Aspect 56, Aspect 57, Aspect 58, Aspect 59, Aspect 60, Aspect 61, Aspect 62, Aspect 63, Aspect 64, Aspect 65, Aspect 66, Aspect 67, Aspect 68, Aspect 69 or Aspect 70, wherein the glass composition exhibits a Young's modulus of about 50 GPa to about 65 GPa, a Young's modulus of about 50×10 -7 C -1 - Approx. 95×10 -7 C -1 The expansion coefficient is about 330kgf / mm under a load of 1kgf. 2 -About 480kgf / mm 2 Vickers hardness, and / or exhibit crack resistance under Vickers diamond micro-dimpling of at least 0.4kgf (e.g., at least 0.8kgf, greater than about 1kgf, 0.8kgf-1kgf, 0.4kgf-1kgf, etc.). Aspect 72. An article comprising the glass composition of any of Aspects 56-71, for example, the article can be of the type of tableware, cutlery, cookware, plate glass, windows, windshields, hollow vessels, jars, art and craft glass objects, laser matrix materials, optical fibers, hollow fibers, or laboratory-usable containers. Aspect 73. A method for manufacturing glass, comprising (a) providing raw materials for forming the glass composition described in any of Aspects 56-71 and forming a homogeneous mixture of the raw materials, (b) melting the mixture at a temperature of about 1,000°C to less than or equal to about 1,300°C; and (c) cooling the composition to form a glass composition. The claims are not intended to include, and should not be interpreted as including, means-plus-function or step-plus-function limitations unless such limitations are explicitly recited in a given claim using the phrases "means for" or "step for," respectively. It is contemplated that specific features described individually or as part of an embodiment may be combined with other individually described features or portions of other embodiments. Thus, elements and acts of the various embodiments described herein may be combined to provide additional embodiments. Thus, while certain exemplary embodiments of the methods, articles, glass compositions, and methods of making and using the same have been shown and described above, it is to be clearly understood that the invention is not limited thereto, but may be otherwise variously embodied and practiced within the scope of the following claims.
Claims
1. A glass composition comprising 35-50 mol % of P2O5, 5-15 mol % of SiO2 and 1.5-5 mol % of Al2O3.
2. The glass composition of claim 1, wherein the glass composition has 40-45 mol % P2O5 and 2-4 mol % Al2O3.
3. The glass composition according to claim 1 or 2, further comprising CaO, MgO, Na2O, K2O and ZnO in a total amount of 30-50 mol%.
4. The glass composition of claim 1, claim 2 or claim 3, wherein K2O is less than or equal to 10 mol%.
5. The glass composition of claim 1, claim 2, claim 3 or claim 4, wherein Na2O is less than or equal to 20 mol% or less than or equal to 15 mol%.
6. The glass composition of claim 1, claim 2, claim 3, claim 4 or claim 5 wherein the CaO is at least 20 mol% and not more than 40 mol%.
7. The glass composition of claim 1, claim 2, claim 3, claim 4, claim 5 or claim 6, wherein the glass composition further comprises greater than 0 mol % Fe2O3 and no greater than 0.5 mol % Fe2O3.
8. The glass composition of claim 1, claim 2, claim 3, claim 4, claim 5, claim 6 or claim 7, wherein the total amount of alkali metal oxides in the glass composition does not exceed 14 mol%.
9. The glass composition of claim 1, claim 2, claim 3, claim 4, claim 5, claim 6, claim 7 or claim 8, wherein the total amount of MgO and ZnO is greater than 0 mol% and not greater than 30 mol%.
10. The glass composition of claim 1, claim 2, claim 3, claim 4, claim 5, claim 6, claim 7, claim 8 or claim 9, wherein the glass composition is substantially free of ZnO.
11. The glass composition of claim 1, claim 2, claim 3, claim 4, claim 5, claim 6, claim 7, claim 8, claim 9 or claim 10, wherein the glass composition is substantially free of alkali metal oxides.
12. The glass composition of claim 1, claim 2, claim 3, claim 4, claim 5, claim 6, claim 7, claim 8, claim 9 or claim 10, wherein the glass composition has a total amount of alkali metal oxides of up to 10 mol%.
13. The glass composition of claim 1, claim 2, claim 3, claim 4, claim 5, claim 6, claim 7, claim 8, claim 9, claim 10, claim 11 or claim 12, wherein the glass composition further comprises one or more transition metal oxides, the transition metal oxides comprising oxides of copper, nickel, cobalt, chromium, silver, tin, or any combination thereof.
14. According to claim 1, claim 2, claim 3, claim 4, Claim 5, Claim 6, Claim 7, Claim 8, Claim 9, The glass composition of claim 10, claim 11, claim 12 or claim 13, wherein the glass composition has one or more of the following: The melting point of the glass composition is lower than 1300°C. The glass composition exhibits a glass transition temperature of about 449° C. to about 600° C.; the glass composition exhibits a Young's modulus of about 50 GPa to about 65 GPa, The expansion coefficient of the glass composition is about 50×10 -7 C -1 - Approx. 95×10 -7 C -1 , The glass composition has a strength of about 330 kgf / mm under a load of 1 kgf. 2 To about 480kgf / mm 2 Vickers hardness, and / or The glass composition has a crack resistance of at least 0.4 kgf under Vickers diamond microindentation.
15. An article comprising the glass composition of any one of claims 1 to 14.
16. A method for manufacturing glass, comprising: (a) providing raw materials for forming the glass composition according to any one of claims 1 to 14 and forming a homogeneous mixture of the raw materials, (b) melting the mixture at a temperature of about 1000° C. to less than or equal to about 1300° C.; and (c) cooling the composition to form the glass composition.